Determination of Pleiotropic Effect of Warfarin in VKORC1 and CYP2C9 Genotypes in Patients With Heart Valve Replacement - Shafique, Huma; Ashraf, Naeem Mahmood; Rashid, Amir; Majeed, Asifa; Afsar, Tayyaba; Daly, Ann K.; Almajwal, Ali; Alruwaili, Nawaf W.; Khan, Azmat Ullah; Razak, Suhail (Frontiers in Cardiovascular Medicine, 2022)
Warfarin has been widely used as an oral anticoagulant agent. In past, efforts have been done to study the contribution of genetic variation on warfarin dose requirements. The possible therapeutic dose determination of warfarin is very challenging, i.e., extremely low dose leading to unusable antithrombotic therapy or high dose causes particularly bleeding complications. Our study aimed to investigate these observations in more detail, we determined the correlation of interleukin-6 (IL-6), cyclooxygenase-2 (COX-2), and tumor necrosis factor-α (TNF-α) among VKORC1 and CYP2C9 genetic variants in patients with heart valve replacement who were treated with a range of warfarin doses and compared with levels in healthy controls. A total of 107 human subjects were recruited with low < 5 mg, medium 5–10 mg/day, and high > 10 mg/day warfarin doses. The genetic study of VKORC1–1639G/A, C1173T, 3730G > A, CYP2C9*2, and CYP2C9*3 was performed using TaqMan genotyping and DNA sequencing. The gene expression of IL-6, TNF-α, and COX-2 mRNA was analyzed. IL-6, TNF-α, and COX-2 protein expressions were determined by ELISA and Western blot analysis to evaluate the pro- and anti-inflammatory effects of warfarin. A statistically significant difference was found among the haplotypes of VKORC1 rs9934438 (C1173T), rs9923231 (−1639G > A), rs7294 (3730G > A) and CYP2C9 *2 p. Arg144 Cys (rs28371674), CYP2C9 *3 p. Ile359Leu (rs1057910) genotypes with warfarin dose requirements (p = 0.001). The increased levels of COX-2, IL-6, and TNF-α proteins were observed when a high dose of warfarin (>10 mg/ml) was administered. However, a lower concentration (1.0 mg/ml) was observed with decreased warfarin dose (<5 mg/day). The present study reported that in addition to its anticoagulant action, the genetic variants of warfarin may have a pleiotropic effect by influencing IL-6 depending on the dosing regimen and inducing the expression of COX-2.